Haploseek: A new 24-hour all-in-one method for combined PGT of monogenic diseases (PGT-M) chromosomal rearrangements (PGT-SR) and aneuploidy (PGT-A). (April 2019) - Zeevi, David A.; Backenroth, Daniel; Carmi, Shai; Zahdeh, Fouad; Kling, Yehuda; Perez, Aaron; Rosen, Tzvia; Levy-Lahad, Ephrat; Altarescu, Gheona
Abstract : Introduction: Recent technological advances have enabled combined gene mutation detection and comprehensive chromosome screening (CCS) from a single embryo biopsy by means of microarray or high coverage next generation sequencing (NGS) technologies. However, these methods are still challenging, very expensive, time consuming, and therefore not widely applied. Therefore, the aim of this study was to develop an economical, user-friendly, all-in-one NGS-based workflow for gene mutation detection combined with CCS screening while maintaining the highest standard for accuracy in a 24 hour workflow protocol. Materials & Methods: Three families, of 3-4 children each, were recruited at the Shaare Zedek Medical Center, Jerusalem, Israel. For each family, whole genome haplotype phasing of the parents was accomplished by SNP microarray genotyping analysis of the couple and one child. From the other children in each family, lymphoblast cultures were prepared and single cells were isolated so that each child would be represented by one cell only. Subsequently, each child's single cell isolate was subjected to low genomic coverage (1x) single read (1 × 50) whole genome sequencing on a NextSeq 500 instrument followed by combined chromosome copy number assessment (PGT-A/PGT-SR) and whole genome haplotype phasing for PGT-M. Sequencing reads were aligned to the reference human genome followed by crude variant calling at SNP positions matching those on the trio-phased SNP microarrays. Custom R scripts were devised to integrate trio-phased microarray data and low coverage sequencing data so as to predict paternal and maternal haplotypes throughout the genomes of each sequenced sample. In addition, a custom user-friendly software, termed, 'haploseek', was created to visualize data output on a web browser in two plots depicting haplotype prediction and marginal haplotype probability, respectively. For copy number variant (CNV) prediction, a custom CNV detection R script was devised and plotted by web browser. All single cell haplotype and CNV predictions were validated by SNP microarray analysis of bulk genomic peripheral blood DNA from the corresponding tissue culture donor. The entire single cell sequencing assay was completed within 24 hours, beginning from single cell isolation until test result conclusion. Results: Whole genome copy number assessment and haplotype phasing of the single cell sequencing data was completely (100%) concordant with known, microarray determined, whole genome chromosome copy numbers and haplotypes in each child from all 3 families. Interestingly, a relatively long segmental deletion of chr21q was identified in the single cell sequencing data of one of the children together with haplotype information suggesting that the deleted allele was paternal in origin. This result and all other copy number assessments in the low coverage data were confirmed by array validation as well. Conclusions: Our results demonstrate the establishment of a reliable method for all-in-one molecular and chromosomal diagnosis of single cells. Importantly, the whole 'Haploseek' process was predicated upon rapid sample processing, rapid sequencing, stream-lined analysis, and user-friendly result reporting so as to expedite clinical implementation. Thus, our novel NGS –based method may become the ultimate, economically feasible, 24 hour end-to-end solution for combined PGT-M, PGT-SR and PGT-A application.